Rewriting the rules: How U.S. tariff paths could reshape global trade - Piñeiro, Valeria; Gianatiempo, Juan Pablo; Rueda, Jorge Armando; Glauber, Joseph W. (International Food Policy Research Institute, 2025)
This paper examines how the recent shift in United States tariff policy could reshape global agricultural trade and influence the stability of food systems worldwide. Using the MIRAGRODEP computable general equilibrium model, the analysis evaluates three policy scenarios that reflect the current trajectory of trade tensions: the North America scenario, the Liberation Day tariff package, and a renewed U.S.–China tariff confrontation. The scenario results reveal distinct lessons. The North America scenario shows that deeply integrated regional markets are extremely sensitive to tariff shocks, and even moderate tariff increases within North America lead to significant disruptions in agricultural trade and measurable welfare losses for Canada and Mexico. The Liberation Day scenario demonstrates that unilateral tariff escalation reduces U.S. competitiveness across a wide range of agricultural products and triggers substantial trade diversion toward countries with preferential access, particularly Mexico, which becomes the primary beneficiary of redirected U.S. import demand. The China scenario highlights that renewed U.S.–China tariff escalation produces severe distortions, especially in oilseed markets, as prohibitive tariffs drive China to shift its purchases almost entirely toward South American suppliers, sharply lowering U.S. export prices and fragmenting global supply chains. Across all scenarios, global agricultural trade contracts, supply chains become less efficient, and food systems become more exposed to climate and geopolitical shocks. These findings underscore the need for predictable and coordinated trade policies that limit uncertainty rather than amplify it. Strengthening trade diversification, investing in supply chain resilience, and aligning economic and geopolitical objectives remain essential for safeguarding global food security in an increasingly unstable trade environment.